Estimation of linear hydrodynamic derivatives of a 37000 tdw chemical tanker using virtual captive model tests - Florentin Daniel Popa; Radu Bosoancă (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding, 2023)
Forecasting the hydrodynamic properties of a ship is crucial for assessing its maneuvering capabilities. This study presents the results of static drift and circular motion simulations conducted on a 37000 tdw chemical tanker. The calculations were carried out using the ISIS-CFD solver, accessible through the FineTM/Marine academic license provided by NUMECA. The flow solution was obtained by numerically solving the Reynolds-Averaged Navier Stokes equations, employing the k-ω Shear Stress Transport (SST) model to represent turbulence. The simulation results were used to determine the linear hydrodynamic derivatives, which were then compared with hydrodynamic derivatives estimated with empirical formulas proposed by Clarke et. al. [1] and Tribon Initial Design module in the absence of experimental results.